Behavioral evidence for the differential regulation of p-p38 MAPK and p-NF-κB in rats with trigeminal neuropathic pain - Lee Min K; Han Seung R; Park Min K; Kim Min J; Bae Yong C; Kim Sung K; Park Jae S; Ahn Dong K (SAGE Publishing, 2011)
Abstract Background We investigated the differential regulation of p-p38 MAPK or p-NF-κB in male Sprague-Dawley rats with inferior alveolar nerve injury resulting from mal-positioned dental implants. For this purpose, we characterized the temporal expression of p-p38 MAPK or p-NF-κB in the medullary dorsal horn and examined changes in nociceptive behavior after a blockade of p-p38 MAPK or p-NF-κB pathways in rats with trigeminal neuropathic pain. Results Under anesthesia, the left lower second molar was extracted and replaced with a mini dental implant to intentionally injure the inferior alveolar nerve. Western and immunofluorescence analysis revealed that p-p38 MAPK is upregulated in microglia following nerve injury and that this expression peaked on postoperative day (POD) 3 through 7. However, the activation of p-NF-κB in astrocyte peaked on POD 7 through 21. The intracisternal administration of SB203580 (1 or 10 μg), a p38 MAPK inhibitor, on POD 3 but not on POD 21 markedly inhibits mechanical allodynia and the p-p38 MAPK expression. However, the intracisternal administration of SN50 (0.2 or 2 ng), an NF-κB inhibitor, on POD 21 but not on POD 3 attenuates mechanical allodynia and p-NF-κB expression. Dexamethasone (25 mg/kg) decreases not only the activation of p38 MAPK but also that of NF-κB on POD 7. Conclusions These results suggest that early expression of p-p38 MAPK in the microglia and late induction of p-NF-κB in astrocyte play an important role in trigeminal neuropathic pain and that a blockade of p-p38 MAPK at an early stage and p-NF-κB at a late stage might be a potential therapeutic strategy for treatment of trigeminal neuropathic pain.